Annie Oakley - Hamilton, John (Edina, MN : Abdo & Daughters, 1996)
A biography of the markswoman and performer who achieved fame with Buffalo Bill Cody's Wild West Show.
Includes bibliographical references and index.
Keywords: Oakley, Annie; Shooters of firearms -- United States; Frontier and pioneer life -- West (U.S.); Entertainers; Sharpshooters; Women